Penerapan Model Talking Stick Berbantuan Flashcard Untuk Meningkatkan Proses Dan Hasil Belajar IPAS Pesera Didik Kelas IV - Selpiani Putri; Sundahry; Tri Wera Agrita (CV. DIGITIAL EDUKASI NUSANTARA, 2026)
Abstract The low learning process and learning outcomes in Science and Social Studies (IPAS) among fourth grade students were caused by teacher-centered learning and the limited use of learning media. This study aimed to improve the learning process and learning outcomes in IPAS through the implementation of the Talking Stick model assisted by Flashcard media for fourth grade students at SDN 050/II Lubuk Landai. This study employed Classroom Action Research (CAR) conducted in two cycles involving 20 fourth grade students. Data were collected through observation, tests, and documentation using observation sheets and test questions. The data were analyzed qualitatively and quantitatively. The results showed that the teacher’s learning process improved from 65% to 92.5%, the students’ learning process improved from 45% to 85%, and learning mastery improved from 40% to 85%. Therefore, the implementation of the Talking Stick model assisted by Flashcard media was able to improve the learning process and learning outcomes in IPAS among fourth grade students at SDN 050/II Lubuk Landai. Keywords: Learning Process; Learning Outcomes; IPAS; Talking Stick; Flashcard.